Corporate personhood / Susanna Kim Ripken. - Ripken, Susanna Kim (Cambridge University Press, 2019)
The topic of corporate personhood has captured the attention of many who are concerned about the increasing presence, power, and influence of corporations in modern society. Recent Supreme Court cases like Citizens United, Hobby Lobby, and Masterpiece Cakeshop - which solidified the free speech and religious liberty rights of corporations and their owners - have heightened the controversy over treating corporations as persons under the law. What does it mean to say that the corporation is a person, and why does it matter? In Corporate Personhood, Susanna Kim Ripken addresses these questions and highlights the complexity of the corporate personhood concept. Using a broad, interdisciplinary framework - incorporating law, economics, philosophy, sociology, psychology, organizational theory, political science, and linguistics - this highly original work explores the complex, multidimensional nature of corporate personhood and its implications for corporate rights and duties.